Study on the Technology Conditions of Flue Gas Desulfurization with Organic Solvent - Chen, Wanren; Li, Hua; Chen, Xiaoshuang (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
The technology experiment on Flue Gas Desulfurization (FDG) by DMSO method is studied in this paper, and the desulfurization efficiency is set out in various conditions. The results show that the desulfurization efficiency can be over 94% under the condition as follows: the rate of flow of DMSO=100 L/h, L/Gï¼40ï½ž50, absorbent concentration = 100 %DMSO, T=room temperature, the gas flow=60 mlâˆ™min-1, inlet SO2 concentration= 0.1-0.5 %, the time of operation must be controlled in 30 minutes.